2015
DOI: 10.2471/blt.14.145623
|View full text |Cite
|
Sign up to set email alerts
|

Using patient-held records to evaluate contraceptive use in Malawi

Abstract: ObjectiveTo investigate a method of using patient-held records to collect contraception data in Malawi, that could be used to explore contraceptive discontinuation and method switching.MethodsIn 2012, all 7393 women aged 15 to 49 years living in the area covered by the Karonga demographic surveillance site were offered a family planning card, which was attached to the woman’s health passport – a patient-held medical record. Health-care providers were trained to use the cards to record details of contraception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(12 reference statements)
0
10
1
Order By: Relevance
“…Of the 7,393 eligible women, 6,861 (93%) were issued a family planning card and 4,678 (63%) submitted their card after one year; participants’ mean age was 30.4 years, and the average observation time was 383 days (range, 122–519; standard deviation, 38). Nonparticipants were slightly younger, were more likely to be never married and were more educated than women who participated 30. Overall, 43% of participants used a modern method of contraception (excluding condoms) at some point during the study period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 7,393 eligible women, 6,861 (93%) were issued a family planning card and 4,678 (63%) submitted their card after one year; participants’ mean age was 30.4 years, and the average observation time was 383 days (range, 122–519; standard deviation, 38). Nonparticipants were slightly younger, were more likely to be never married and were more educated than women who participated 30. Overall, 43% of participants used a modern method of contraception (excluding condoms) at some point during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Informed written consent for the collection and analysis of data was obtained from the study participants upon collection of the family planning cards. More detailed methods and an evaluation of the success of the data collection are described elsewhere 30…”
Section: Methodsmentioning
confidence: 99%
“…All 132 health care providers working in the study catchment area were trained to record information on the FP cards whenever they provided contraception to a woman holding a card. Multiple refresher trainings were conducted, mobile phone air time was provided and motivational text messages were sent to health care providers, to keep them engaged [15].…”
Section: Study Setting and Methodsmentioning
confidence: 99%
“…Contraceptive users and family planning providers alike noted how helpful providers can be in warning new users about the likely experience of side effects -as well as with switching if side effects became unbearable. Many researchers have concluded the importance of quality family planning services -in particular, family planning provider counseling on the anticipated side effects and switching as one deterrent to contraceptive discontinuation (2)(3)(4)6,7,10,11,14,(22)(23)(24)(25)(26)(27)(28); while others suggest that programs and providers have little impact on continuation (13,17). One study analyzed the correlation between discontinuation rates and family planning program effort scores, and found a negative relationship, albeit weak, and concluded that family planning programs can impact discontinuation, particularly in terms of training and supervision of providers (5).…”
Section: Resultsmentioning
confidence: 99%
“…Switching from one method to another method is the ideal course of action for women and couples who desire to continue to prevent pregnancy but are not satisfied with their current method. In a study in Malawi switching within three months of discontinuation was just 4%, while in a study in Kenya, 63% of discontinuers had switched to another method within three months of discontinuation (16) , (17). A study examining switching in 23 low and middle income countries found switching to be around 60% within three months (15).…”
mentioning
confidence: 99%